SOCIO-PSYCHOLOGICAL CONDITIONS OF FAVORABLE ADAPTATION OF THE GERONTOLOGICAL GROUP OF THE POPULATION TO THE NEW CONDITIONS OF SOCIALIZATION (Psychology Travelogs, 2021)
The article considers the socio-psychological conditions of adaptation of the elderly to aging and the impact of social status on this process: household (quality of food, which allows us to consider an external factor of social adaptation); leisure (leisure organization); communication (communication helps the elderly to share life experiences and just find like-minded people); religious; the practice of "dream realization" used in Poland (social workers, psychologists help their clients to realize a "small" dream). The main "life positions" (constructive, dependent, protective, position of "hostility to the world", position of "hostility to oneself and one's life") of this category of persons influencing psychological adaptability are studied. Forms of social adaptation are classified, which distinguish conformism, innovation, ritualism, retreatism, radicalism (rebellion), the study found that the most common forms of adaptation for all the elderly are ritualism and conformism. The conditions of favorable adaptation of the elderly to the new conditions of socialization are substantiated through the prism of social and psychological rehabilitation, which consists in social security, care, protection. The tasks of a social worker, a practical psychologist in the organization of social and psychological adaptation, the elderly are analyzed. The strategy of social and psychological work with single elderly people is described. The influence of social status on the adaptation process in old age is determined. The concept of loneliness in the aspect of social protection is considered.
Keywords: adaptation; socialization; the elderly; social security; socio-psychological rehabilitation; care